2008
DOI: 10.1177/1523422308324666
|View full text |Cite
|
Sign up to set email alerts
|

Development Economics: A Foundation for HRD Policy Studies in Developing Countries

Abstract: The problem and the solution . Theoretical work in development economics has had a significant impact on the development process of nations, including national policies for human resource development (HRD) in developing countries.As an important component of an overall economic development system, HRD can benefit from the insights provided by development economics—especially in developing countries. At the national policy level, HRD should identify and pursue opportunities for economic development by engaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…According to the definition of the World Bank, GDP represents the sum of value added by all its producers, while value added is the value of the gross output less the value of intermediate goods and services consumed in the process of production, before accounting for consumption of fixed capital in production. According to some authors [1,20], after the World War II, the main objective for advanced economies was to maintain a specific target of GDP growth, starting from the assumption that a high level of GDP will automatically bring in a higher level for economic welfare and quality of life. Subsequently, many scholars started to underline the differences between economic growth and sustainable development [1].…”
Section: The Country-level Governance Versus Economic Growth-backgroumentioning
confidence: 99%
“…According to the definition of the World Bank, GDP represents the sum of value added by all its producers, while value added is the value of the gross output less the value of intermediate goods and services consumed in the process of production, before accounting for consumption of fixed capital in production. According to some authors [1,20], after the World War II, the main objective for advanced economies was to maintain a specific target of GDP growth, starting from the assumption that a high level of GDP will automatically bring in a higher level for economic welfare and quality of life. Subsequently, many scholars started to underline the differences between economic growth and sustainable development [1].…”
Section: The Country-level Governance Versus Economic Growth-backgroumentioning
confidence: 99%
“…In the period from the fifties to the eighties the dominant approach to development was based on orientation to increase the economic growth (Khan, 2007). After the World War II the main issue for developed countries was to maintain the economic growth while developing countries focused their attention on achieving the target of GDP growth which would, as it was assumed, automatically lead to a higher level of quality of life (Wang et al, 2008). Some scholars point out the difference between growth and development and scholars are slowly beginning to embrace these differences.…”
Section: From Economic Growth To Sustainable Developmentmentioning
confidence: 99%
“…McLean's work was followed by Cho and McLean (2004), on empirical findings, Wang et al (2008), about developing countries, Wang (2008) studying critical aspects of the paradigm itself, Burkhardt and Bennett (2015) analyzing globalization and Tkachenko (2015) on the historical roots of the discipline. Nowadays, NHRD achieved worldwide statussearching in a large database such as EBSCO, HRD studies of national scope are found for the OECD countries and also for many developing countries such as China, India, South Africa, Botswana, the Arab Gulf States, Venezuela, Ukraine, Pacific Islands, Venezuela, Jamaica, Kuwait and Kyrgyzstan.…”
Section: Ejtd 437/8mentioning
confidence: 99%